Delocalized quantum states enhance photocell efficiency. Issue 8 (27th January 2015) - Zhang, Yiteng; Oh, Sangchul; Alharbi, Fahhad H.; Engel, Gregory S.; Kais, Sabre
Abstract : The high quantum efficiency of photosynthetic complexes has inspired researchers to explore new routes to utilize this process for photovoltaic devices. Abstract : The high quantum efficiency of photosynthetic complexes has inspired researchers to explore new routes to utilize this process for photovoltaic devices. Quantum coherence has been demonstrated to play a crucial role in this process. Herein, we propose a three-dipole system as a model of a new photocell type which exploits the coherence among its three dipoles. We have proved that the efficiency of such a photocell is greatly enhanced by quantum coherence. We have also predicted that the photocurrents can be enhanced by about 49.5% in such a coherent coupled dipole system compared with the uncoupled dipoles. These results suggest a promising novel design aspect of photosynthesis-mimicking photovoltaic devices.